Comunicación Audiovisual y Educación: un itinerario interactivamente significativo - Ruiz Vallejos, Fernando Federico (2007)
This article is an itinerary review of Communication and Education from the 20th century to our days. Basing in quotes and reflections we could briefly appreciate the essential dialogue between both disciplines.